2015
DOI: 10.3109/08923973.2015.1082584
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory effects of barettin and involvement of the kinases CAMK1α and RIPK2

Abstract: The anti-inflammatory activity of barettin is exerted through the regulation of inflammatory mediators such as MCP-1 and IL-10, possibly via inhibition of kinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…There are few inhibitors of CAMK1 that have been identified to date (such as Barettin 72 or pyridine amides 73 ), which have a role in inflammation targeting IL-10. 72 Previous in vitro work has shown that inhibiting CAMK1 in cells reduces IL-10, the master anti-inflammatory interleukin. 74 In the present study, there is no significant difference in the IL-10 levels between the untreated and pyronaridine-treated infected groups so it seems unlikely that CAMK1 inhibition would be involved in the mechanism of action of inhibition of SAR-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…There are few inhibitors of CAMK1 that have been identified to date (such as Barettin 72 or pyridine amides 73 ), which have a role in inflammation targeting IL-10. 72 Previous in vitro work has shown that inhibiting CAMK1 in cells reduces IL-10, the master anti-inflammatory interleukin. 74 In the present study, there is no significant difference in the IL-10 levels between the untreated and pyronaridine-treated infected groups so it seems unlikely that CAMK1 inhibition would be involved in the mechanism of action of inhibition of SAR-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have shown that pyronaridine may target Pl pro as well as CAMK1. There are few inhibitors of CAMK1 that have been identified to date (such as Barettin (62) or pyridine amides (63)) which has a role in inflammation targeting IL-10 (62). Previous in vitro work has shown that inhibiting CAMK1 in cells reduces IL-10, the master anti-inflammatory interleukin (64).…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Karianne F. Lind et al reported that barettin ( 70 , Figure 20), which was first isolated and described in 1986 [90], inhibited RIPK2 (IC 50 = 8.0 μM), CAMK1a (IC 50 = 5.7 μM), SIK2 (IC 50 = 6.1 μM) and produced anti-inflammatory effects in vitro [91,92]. In 2015, Rebecca Horbert et al reported the synthetic compound 71 (Figure 20) with a 3,5-diarylpyrazin-2-one core that was based on hamacanthins A and B, which are sponge natural products of the bis-indole alkaloid class [93].…”
Section: Discussionmentioning
confidence: 99%